A case of neoplastic synchronism in a dog. (November 2021) - Rifici, Claudia; Quartuccio, Marco; Sfacteria, Alessandra; Lanteri, Giovanni; Abbate, Jessica Maria; Cristarella, Santo; Mazzullo, Giuseppe
Abstract: Introduction: Synchronous primary tumors are considered severe, comorbid conditions in people representing neoplasm that develop independently and concomitantly. A diagnosis of synchronous tumors was made in a dog, underlying the difficulties to reach it without the aid of multiple diagnostic techniques aimed to demonstrate the simultaneous coexistence of different tumor types. Materials and methods: A 7-year-old male Boxer dog presented several tumors located on the skin of the left hind limb and the scrotal region. Moreover, additional tumors in the testicles, after palpation and ultrasound examination, were detected. Following diagnostic results, the cutaneous tumor, scrotum, and testes were surgically removed. Results: Pathological investigations revealed the presence of five different tumors: a cutaneous mast cell tumor; a scrotal melanocytoma; three testicular neoplasms (Sertoli Sustentacular cell tumor, seminoma, and interstitial Leydig cell tumor). Conclusions: The present report describes a neoplastic synchronism due to the presence of five different primary tumors in a dog and, for the first time the presence of a collision testicular tumor together with other non-testicular primary tumors. The occasional finding underlines the importance of the knowledge of such conditions in the process of decision-making and in carrying out all the proper diagnostic procedures for a correct diagnosis and clinical staging. Highlights: Tumors located on the skin of the left hind limb and the scrotal region in a 7-year-old male Boxer dog. Cutaneous mast cell tumor, Scrotal melanocytoma, Sustentacular tumor, Seminoma and Interstitial cell tumor. Five synchronous primary different tumors including a collision testicular tumour and other non-testicular primary tumors.